The Application of Bass Diffusion Model in Forecasting Telecommunication Services Users in Military Assistance to Civilian Authorities - Pavlovic, Boban Z.; Karovic, Samed M. (Defence Science Journal, 2015)
This paper analyses the application of Bass’s diffusion model in forecasting the number of telecommunication services users in the event of natural disasters. Citizens’ behaviour has been modelled in the case of an emergency situation caused by an earthquake with high magnitude. We analysed the area of an administrative district in the south-west part of the Republic of Serbia which includes two cities and three municipalities. To control the consequences of natural disasters, a unit of the Army of Serbia with the required number of radio transceivers for establishing communication between the vulnerable population and rescuers with command staff at the observed territory has been dimensioned. Special emphasis is given to the provision of telecommunication support in the military assistance in a relief operation with civil authorities. Defence Science Journal, Vol. 65, No. 2, March 2015, pp.144-149, DOI:http://dx.doi.org/10.14429/dsj.65.6026